Parameter Identification and Block Diagram Reduction of DC054B-5 Motor in Electric Control System Application - Muhammad Ihsan P (Journal of Marine Electrical and Electronic Technology, 2025)
Accurate modeling of DC motors plays a crucial role in the development of reliable and responsive electric control systems, especially in industrial automation and embedded applications. This paper presents a detailed modeling approach for the DC motor ElectroCraft DC054B-5, focusing on parameter identification and block diagram reduction for control system design purposes. The modeling process begins with the formulation of electrical and mechanical differential equations based on Kirchhoff’s law and Newton’s second law of motion. These equations are then transformed into the Laplace domain to obtain the motor’s transfer function, representing the system’s input-output dynamics. Key motor parameters such as armature resistance, inductance, torque constant, back-EMF constant, and moment of inertia are derived through a combination of datasheet specifications and analytical calculations. The integration of both electrical and mechanical models results in an electromechanical model that captures the essential behavior of the motor under various load and input conditions. To simplify the control system analysis, block diagram reduction techniques are employed, enabling the transformation of complex systems into manageable control structures. The proposed models are validated using MATLAB/Simulink simulations in both open-loop and closed-loop scenarios. The time response characteristics—including rise time, steady-state speed, and transient behavior—demonstrate good agreement with theoretical expectations. The result provides engineers and researchers with a robust framework for analyzing and designing control strategies for DC motors. This approach enhances the efficiency, accuracy, and safety of motor-driven systems, and is applicable to various electronic and electric technology domains such as robotics, automation, and precision actuation.